Transmission of MDR MRSA between primates, their environment and personnel at a United States primate centre - Soge, Olusegun O. (J Antimicrob Chemother, 2016)
OBJECTIVES: MDR MRSA isolates cultured from primates, their facility and primate personnel from the Washington National Primate Research Center were characterized to determine whether they were epidemiologically related to each other and if they represented common local human-associated MRSA strains. METHODS: Human and primate nasal and composite environmental samples were collected, enriched and selected on medium supplemented with oxacillin and polymyxin B. Isolates were biochemically verified as Staphylococcus aureus and screened for the mecA gene. Selected isolates were characterized using SCCmec typing, MLST and WGS. RESULTS: Nasal cultures were performed on 596 primates and 105 (17.6%) were MRSA positive. Two of 79 (2.5%) personnel and two of 56 (3.6%) composite primate environmental facility samples were MRSA positive. Three MRSA isolates from primates, one MRSA from personnel, two environmental MRSA and one primate MSSA were ST188 and were the same strain type by conventional typing methods. ST188 isolates were related to a 2007 ST188 human isolate from Hong Kong. Both MRSA isolates from out-of-state primates had a novel MLST type, ST3268, and an unrelated group. All isolates carried ≥1 other antibiotic resistance gene(s), including tet(38), the only tet gene identified. CONCLUSIONS: ST188 is very rare in North America and has almost exclusively been identified in people from Pan-Asia, while ST3268 is a newly reported MRSA type. The data suggest that the primate MDR MRSA was unlikely to come from primate centre employees. Captive primates are likely to be an unappreciated source of MRSA.